Hybrid soil-structure interaction approach for the assessment of vibrations in buildings due to railway traffic. (January 2022) - Colaço, A.; Barbosa, D.; Alves Costa, P.
Abstract: The numerical assessment of the dynamic response of buildings exposed to railway traffic usually requires advanced numerical models that take into account the three-dimensional character of the problem. However, engineering practice requires simple and efficient methodologies. Thus, in order to reduce the uncertainties associated with the prediction procedure, a hybrid approach is formulated, combining numerical/experimental results and post-processing techniques. The underlying concept of the methodology is the so-called SSI (soil-structure interaction) curves, which, when applied to the input motion experimentally evaluated in free-field conditions, can replace the kinematic effects induced by the presence of the building, avoiding their consideration in the simulation of wave propagation on the ground. Following the introduction of an innovative and simple approach, a numerical application example involving vibrations induced by railway traffic is presented, clearly showing the potential of the proposed methodology in assessing the building's dynamic response to railway traffic in the vicinity.